Study of Distillation Method and Time on the Quality of Basil (Ocimum sanctum L.) Essential Oil - Soekarno, Siswoyo; Hernanto, Setyawan Dwi; Purbasari, Dian; Melani, Dewi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
"Basil" or basil has economic value both in fresh form, simplicia and essential oil. This research aims to evaluate the method and duration of distillation in making essential oil from basil. Two distillation methods, namely steam and boil distillation, are carried out with different distillation times (1 hour, 2 hours, and 3 hours). The parameters observed were physical characteristics which included oil volume, yield, pH, distillation rate, color, aroma and spots. The results show that the best distillation process time is 2 h for both distillation methods. Steam distillation for 2 hours produced the best essential oil of 1.1 ml, yield 0.11%, pH 5.78, distillation rate of 0.53 ml/h, pale yellow color, strong aroma, clean spots. Meanwhile, water boiled distillation for 2 h produced 1.2 ml of essential oil, 0.12% yield, pH 6.31, distillation rate of 0.60 ml/h, brown color, weak aroma, very spotty. Distillation of basil leaf essential oil using the steam method for 2 h was determined as the best treatment based on the highest essential oil yield, smallest pH, highest distillation rate, clearest color, most distinctive aroma, and cleanest stain. Keywords: Aroma, Basil leaves, Essential oil, Steam distillation, Yield.